2014
DOI: 10.3399/bjgp14x680137
|View full text |Cite
|
Sign up to set email alerts
|

Using a patient-generated mental-health measure ‘PSYCHLOPS’ to explore problems in patients with coronary heart disease

Abstract: BackgroundPatients with coronary heart disease (CHD) who are depressed have an increased risk of further cardiac events and higher mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…They (Psychological Outcome Profiles Questionnaire and Rapid Estimate of Adult Literacy in Medicine) were analysed separately and led to publications, which are listed in the acknowledgments. 197,198 The third (Guy's Hospital Questionnaire) was suggested by the cardiologist on the team but was abandoned because it was too difficult to administer over the telephone. Original data sets downloaded from MACRO by the Data Manager (Christopher Rowson) and emailed as a .csv file Rachel Phillips was responsible for receiving all extractions up to and including the 24-month data RP also wrote the instructions for cleaning the data sets and data checking processes…”
Section: Discussionmentioning
confidence: 99%
“…They (Psychological Outcome Profiles Questionnaire and Rapid Estimate of Adult Literacy in Medicine) were analysed separately and led to publications, which are listed in the acknowledgments. 197,198 The third (Guy's Hospital Questionnaire) was suggested by the cardiologist on the team but was abandoned because it was too difficult to administer over the telephone. Original data sets downloaded from MACRO by the Data Manager (Christopher Rowson) and emailed as a .csv file Rachel Phillips was responsible for receiving all extractions up to and including the 24-month data RP also wrote the instructions for cleaning the data sets and data checking processes…”
Section: Discussionmentioning
confidence: 99%
“…The same seven high-level problem themes were used in a subsequent publication, though were further defined into 61 subthemes for both the problem and the functioning domains of the PSYCHLOPS (Ashworth et al, 2007). Lawton et al (2014) coded three problem and functioning themes (physical, psychological, and social), further stratified into nine subthemes (e.g., social work, social money). Evidence from one of these studies (Ashworth et al, 2007) suggests that the PSYCHLOPS reported problems may be more comprehensive than those captured using a quantitative, fully structured nomothetic instrument.…”
Section: Consideration Of Culture and Individual Experience Is Atmentioning
confidence: 99%
“…Categorisations for PSYCHLOPS have been used previously in three studies from the UK (Ashworth et al, 2007;Lawton et al, 2014;Robinson et al, 2007), but due to the geographical and cultural diversity of the populations under study, researchers used a datadriven approach. Two researchers (MHS and EvtH) independently coded the responses given to the qualitative items of PSYCHLOPS to identify themes in a two-step process.…”
Section: Data Codingmentioning
confidence: 99%
See 2 more Smart Citations